Sweden : Staff Report for the 2012 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
Sweden's recovery from the global crisis was swift reflecting its strong position at the onset of the crisis. The 2012 Article IV Consultation reports that the economic outlook remains clouded. Executive Directors have commended Sweden's sustained strong macroeconomic performance, which has been underpinned by prudent policies and effective institutions. They have also welcomed efforts to strengthen the macroprudential framework and financial sector oversight through tighter capital and liquidity requirements, and have encouraged the authorities to further their cross-border collaboration with regional banking regulators.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet